The Effect of Green Color Therapy for Stress in Elderly in the Elderly Social Institution of Wana Seraya Denpasar. Final - Devi Putu Shinta (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Presentation of elderly group is increasing with all problems that follow. One of the psychological problems that is likely experienced by the elderly is stress. Stress management can be done with non-pharmacological and pharmacological therapies. One of non pharmacological therapies that can affect stress is green color therapy. The green color can make people feel comfortable, relax, reduce stress, balance and calm down the emotions, and stimulate the pituitary to release neurohormones, which can reduce stress. This study aims to determine the therapeutic effect of green color on stress of the elderly in the Elderly Social Institution of Wana Seraya Denpasar. This research is a quasy-experimental study (pre-test and post-test with control group design). Samples consist of 30 elderly people that were selected by purposive sampling, and divided into two ie; control and experimental groups. The experimental group was given green color therapy for 10 minutes every day for seven days. Stress measurement was carried out by using Depression Anxiety Stress Scales (DASS) questionnaire of which the validity and reliability have been tested. The results obtained, the average decrease in stress score of 1.20 in the control group, and in the experimental group gained an average decrease in stress score of 11.80. Based on the independent sample t-test, this difference was statistically significant, with t value of -17.528 and the Sig. (2-tailed) of 0.000, which means there is a therapeutic effect of green color therapy to stress in the elderly in the Elderly Social Institution Wana Seraya Denpasar.